A bald statement – current approaches to manipulate miniaturisation focus only on promoting hair growth - Pantelireis,N; Higgins,C (Experimental Dermatology, 2018)
Hair plays a large part in communication and society with its role changing through time and across cultures. Most people don't leave the house before combing their hair or shaving their beard and for many hair loss or irregular hair growth can have a significant impact on their psychological health. Somewhat unsurprisingly, according to GMR Data today's global hair care industry is worth an estimated $87 Billion in 2018, with hair loss estimated at $2.8 Billion. Considering that no current hair loss related products can completely reverse hair loss, it is reasonable to believe this market could expand significantly with the discovery of a comprehensive therapy. As such, a great deal of research focuses on overcoming hair loss, and in particular, a common form of hair loss known as Androgenetic Alopecia (AGA) or male pattern baldness. In AGA hair follicles miniaturise in a large step change from a terminal to a vellus state. Within this viewpoint article, we discuss how influx and efflux of cells into and out from the dermal papilla can modulate dermal papilla size during the hair cycle. As dermal papilla size is positively correlated with the size of the hair fibre produced by a follicle, we argue here that therapies for treating AGA should be developed which can alter dermal papilla size, rather than just promote hair growth. We also discuss current therapeutics for AGA, and emphasize the importance of using the right model systems to analyse miniaturisation.